Applying STEM Engineering Design Process through Designing and Making of Electrostatic Painting Equipment in Two Rural Schools in Vietnam - Duong, X. Q.; Nguyen, N. H.; Nguyen, M. T.; Thao-Do, T. P. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
STEM education has been emphasized in Vietnam’s new National Education Curriculum to develop students’ capacity and prepare for the modern labor market. However, there are concerns that STEM education may not be suitable for low-budget or rural schools, where the conditions are insufficient. This research aims to investigate the possibility and efficiency of applying STEM education, focused on the Engineering Design Process (EDP), in rural high schools in Vietnam. This paper reported the results of two rounds of research on 96 grade 11 rural students who participated in a STEM project of designing and making electrostatic painting equipment using the EDP as the alignment. The students were from two rural schools of Thap Muoi district, Dong Thap province in Mekong Delta, where education was considered lower than the general standard of Vietnam. Data was collected using qualitative research methods, including teacher’s observation and notes for the whole process, students’ portfolios (worksheets, research diary, diagram and pictures, video clips, messages, and notes), and informal interviews. Triangulations were applied during data collection and analysis. The results showed promising where the students actively engaged in all the stages of the EDP and could accomplish all the requirements. Moreover, compared to round 1, round 2 showed slightly better indicators which means the experience of the teacher is improved the students’ achievement. Therefore, it can be concluded that STEM EDP can be applied with encouraging results even in rural schools.